Association between arterial stiffness and wave reflection with subsequent development of placental-mediated diseases during pregnancy: findings of a systematic review and meta-analysis. Issue 5 (May 2018) - Osman, Mohamed Waseem; Nath, Mintu; Breslin, Eamonn; Khalil, Asma; Webb, David R.; Robinson, Thompson G.; Mousa, Hatem A.
Abstract : Objective: We present a comprehensive systematic review of published literature to examine, whether arterial stiffness and wave reflection measurements during pregnancy differed between healthy patients and patients with placental-mediated diseases including preeclampsia (PET), small for gestational age (SGA), fetal death, and placental abruption, and a quantitative assessment of the findings using the meta-analysis approach. Methods: We searched Medline, Embase, and The Cochrane Library for studies of arterial stiffness in pregnancy, analyzed pregnancy outcomes and conducted the meta-analysis of data evaluated by trimesters of pregnancy. Hemodynamic parameters evaluated included: pulse wave velocity (PWV), augmentation index (AIx), and augmentation index-75 (AIx-75). Results: We screened 2806 citations, reviewed 36 studies and included nine ( n  = 15 923) studies for further quantitative assessment. Compared with healthy pregnancy, measures of arterial stiffness and wave reflection were consistently increased among pregnant women who subsequently developed PET during all trimesters. In the first trimester, mean AIx-75 (%) in the PET group was significantly higher with estimated standardized mean difference (SMD) of 0.90 [95% confidence intervals (95% CI) 0.07–1.73; P  = 0.034]. In the second trimester, the PET group had significantly higher PWV (m/s) with estimated SMD of 1.26 (95% CI 0.22–2.30; P  = 0.018). Concerning the SGA group, mean AIx (%) was greater during the second trimester only: 65.5 (SD 15.6) vs. 57.0 (11.2), P  < 0.01. Conclusion: There is significant increase in arterial stiffness and wave reflection parameters among pregnant women who subsequently developed PET and SGA fetuses. Larger studies with consistent methodological designs are required to evaluate the role and usefulness of arterial stiffness and wave reflection measurements as a screening tool for placental-mediated diseases during pregnancy. Abstract : Supplemental Digital Content is available in the text